К проблемам исторического синтаксиса (иранские параллели к балто-славянским оборотам «номинатив + инфинитив») - Эдельман, Джой Иосифовна (Baltistica, 1987)
On some problems of historical syntax (Iranian parallels to the Balto-Slavic constructions “nominativus cum infinitivo”) The constructions of the Russian “надо земля пахать”-type (containing the infinitive and the object in Nom.) find their parallels in some Iranian languages. These parallels support the standpoint of Yu. Stepanov that such constructions have appeared by means of amalgamation of two copulative constructions: “мне есть (надобѣ) земля” and “земля есть (надобѣ) пахати” (with the passive meaning of infinitive in the second construction). The development of such infinitive constructions in the Iranian languages must be ascribed to the abundance of various copulative constructions with the meaning of possession, state, debitiveness, possibility, resultativeness, etc., and to the process of contamination of some of them. In its turn, this state is due to the absence (in most of the Iranian languages) or to the “weak” position in the language system (in the rest of them) of the verb “to have”. The situation seems to be supported by the influence of a substratum, i.e. non-Indo-European languages of the area, which did not possess this verb. We may presume then that the substratum influence of the Finno-Ugric languages (which in their majority also do not possess the verb “to have”) upon part of the Balto-Slavic languages was an analogous one: it has held back the development of the verb “to have”, it “weakened” its position in the language system (especially an auxiliary one) and supported the development of various copulative constructions.